SILENCE OF STUDENTS IN EFL CLASSROOM AT ATDS - Eka Trisnawati Sirait; Sri Minda Murni; Sumarsih Sumarsih (LINGUISTIK TERAPAN, 2019)
This study was aimed at examining the Silence of students in EFL Classroom. The objectives of this study were to find out the types and the reason of silence is used by students in Industry Engineering. This study was conducted by descriptive qualitative method. The source of data was recording and interview. The technique of data collection was recording and interview. The technique of data analysis was interactive model by Miles, Huberman and Saldana (2014). The findings of the study showed that: ATDS students in EFL classroom just uses 9 types out of 12 types of silence. They are: (1)The wise or virtuous silent, (2) The modest silent,(3)The cunning silent, (4)The eloquent silent, (5)The dumb founded silent, (6) The culpable silent, (7)The strong silent, (8)The weak silent, (9) The dead silent.Keywords: Silence, EFL Classroom